A Characterization of the SSD-Efficient Frontier of Portfolio Weights by Means of a Set of Mixed-Integer Linear Constraints - Longarela, Iñaki R. (Management Science, 2016)
In this paper, the set of all second-order stochastic dominance (SSD)-efficient portfolios is characterized by using a series of mixed-integer linear constraints. Our derivation employs a combination of the first-order conditions of the utility maximization problem together with a judicious use of binary variables. This result opens the door to the formulation of optimizations whose objective function is free to select a particular portfolio out of the entire SSD-efficient set. This paper was accepted by Jerome Detemple, finance.